ANALYSIS ON THE INFLUENCE OF PRESSURE ADJUSTMENT REFERENCE IN PRESSURE GAUGE CALIBRATION BASED ON DKD-R 6-1: 2014 GUIDELINE - Adindra Vickar Ega; Rudi Anggoro Samodro (LIPI Press, Anggota IKAPI, 2017)
DKD-R 6-1 is a widely used reference document in pressure measuring device (PMD) calibration. However, many of the users do not understand exactly the substance of it. As for example the pressure adjustment during the calibration is based on the reference (STD) reading or the unit under test (UUT) reading, according to the DKD-R 6-1 clause 7 Calibration Method. Therefore, in this research, calibration of barometer as one of PMD, from range 850 hPa to 1050 hPa has been performed to analyze the influence of those two methods to the calibration results and the difficulty or ease in measurement process. The result shows that both methods has different correction of 0,01 hPa, relevant with the uncertainty claim of 0,06 hPa at 850 hPa and 0,05 hPa at 1050 hPa respectively. Measurement by pressure adjustment according to the UUT reading is easier to be performed since UUT has less digit resolution than the reference standard. However, the reading stability of the reference standard needs to be taken into account since it has more digit resolution, in order to get more accurate measurement results. Keywords : barometer, pressure adjustment, DKD-R 6-1, reference standard, UUT